Education Management Based On Multiple Intelligence For Developing The Potential Of Students - Fathor Rakhman; Miftahus Surur; Akhmad Ramli; Anita Noviyanti; Yenny Anggreini Sarumaha (Program Studi Manajemen Pendidikan Islam, Fakultas Tarbiyah, Institut Pesantren Sunan Drajat Lamongan, 2023)
The purpose of this study is to understand how the management of education functions and how the school recognizes and maximizes each student's potential. With an interactive qualitative approach and a case study format, this study employs a qualitative descriptive method. Employing observation, interviewing, and documenting techniques to gather research data. According to the study's findings, education management is carried out in accordance with eight national education standards, including those for content, graduation, processes, facilities and infrastructure, management, financing, assessment, and educator and education staff. Every student is unique and has varied potential, according to school administration. Additionally, it is consistent in implementing a multiple intelligence system in which every student goes through the stages of Multiple Intelligences Research (MIR), which is research carried out by a team to discover the type of intelligence or potential possessed by each student. By knowing this type of intelligence, teachers can apply teaching techniques or strategies that are suitable for students' learning preferences. In order for each child to develop in accordance with his or her talents and interests.